Bonding and Cleaning Effects of Irrigation Protocols Using Calcium Hypochlorite on the Post-space Radicular Dentin - Besegato, J. F.; Bravo, G. R. [UNESP]; Zaniboni, J. F. [UNESP]; Belizário, L. G. [UNESP]; de Almeida, Enm [UNESP]; Gelio, M. B. [UNESP]; Escalante-Otárola, W. G.; Kuga, M. C. [UNESP] (Operative Dentistry, 2024)
This study evaluated the effect of 2.5% sodium hypochlorite (SH) or calcium hypochlorite (CH) submitted to passive ultrasonic irrigation (PUI) or conventional irrigation (CI) on the incidence of residues and the bond strength of the cementation system to post-space dentin. Distilled water (DW) and 2.5% SH followed by 17% EDTA (SH-ED) were used as negative and positive control groups, respectively. The cervical, middle, and apical thirds of the post space were evaluated. One hundred and twenty bovine incisors were endodontically treated and post-space preparation was performed. The specimens were randomly assigned to six groups, according to the solution and irrigation method: DW-CI, SH-ED-CI-SH, SH-CI, SH-PUI, CH-CI, and CH-PUI. The incidence of residues (n=10) over the dentin was evaluated by scores using SEM images. Other specimens were irrigated as previously described and the post cementation was immediately performed using a conventional dual resin cement and a two-step etch-and-rinse adhesive system. Push-out and failure modes were performed for bonding evaluation. Kruskal-Wallis and Dunn test for incidence of residues data and one-way ANOVA and Tukey tests for bond strength data were used at a significance level of 5%. The protocols that showed a lower incidence of residues were: SH-ED-CI-SH, SH-PUI, and CH-PUI for the cervical third and SH-ED-CI-SH for the middle third (p<0.05). In the apical third, the protocols were similar to each other (p>0.05). Bond strength values were higher after irrigation with DW-CI for all thirds (p<0.05). 2.5% sodium or calcium hypochlorite negatively impacted the adhesion interface and exhibited a greater incidence of residues over the post-space radicular dentin.